World Governance Indicators and Fraud: Evidence from One Belt One Road Countries - Kwadwo, ANTWI Stephen; Yusheng, KONG; Mohammed, MUSAH; Mary, DONKOR (The Economics and Finance Letters, 2021)
This paper investigates the effect of worldwide governance indicators and global competitiveness on the level of accounting fraud in One Belt One Road (OBOR) countries. We use publicly available data from various sources. We perform principal components analysis to reduce the six governance indicators to three governance indexes. Governance indicators have significant impact on fraud and the effect could be positive or negative depending on the dimensions involved. Voice and accountability and political stability show significant negative impact on the number of fraud cases. Competitiveness shows a positive but insignificant effect on the level of fraud cases. Democratic countries report lesser number of fraud cases. The findings should be read with caution because of the diversity in the countries in the sample. OBOR countries exhibit different governance models, which may affect their indicators and as a result, the extent of fraud cases reported may be influenced by the regime practiced by a country. The study considers the relevance of governance indicators to policymakers in dealing with rising level of fraud since fraudulent activities affect productivity. Fraud analysis should be embedded in the governance architecture of countries to stimulate development and mitigate the risks of bankruptcies, business failures and loss of investments.